A novel senolytic drug, seno-7284 ameliorates aging phenotype and age-related cardiometabolic diseases. (25th November 2020) - Katsuumi, G; Shimizu, I; Suda, M; Yoshida, Y; Hayashi, Y; Nakao, M; Furuuchi, R; Hsiao, Y.T; Minamino, T
Abstract: Background: Cellular senescence occurs as a result of various genotoxic stresses and it plays a pivotal role in aging and age-related disorders. Recently, it was shown that elimination of senescent cells, so-called "senolysis" has the potential to become a promising novel therapy for age-related disorders in several mice models including cardiovascular diseases. However, there is no senolytic drug available in clinical settings currently. Purpose: The present study was aimed to identify a novel senolytic reagent effective for cardiometabolic disease among compounds already available in clinical settings. Here we demonstrate that a compound called "seno-7284" exhibits senolytic effect in murine models of type 2 diabetes, atherosclerosis, progeroid and chronological aging. Methods: We generated diet-induced obesity/diabetic mice model by imposing high-fat diet from 4-week-old for two months, atherosclerosis mice model by imposing western diet to ApoE homozygous knockout mice (ApoE-KO mice) from 4-week-old for 3 months. We administered seno-7284 mixed in the diet (0.03% w/w) to each mouse model for 1, 2 or 4 weeks. For the analysis, we carried out some physiological examinations including glucose tolerance test (GTT) and insulin tolerance test (ITT), then harvested tissue samples and took them to molecular biological analysis including real-time PCR, western blotting, RNA-sequence, etc. We also generated Zmpste24 homozygous knockout mice (Zmpste24-KO mice) as a progeroid mice model to measure their lifespan. Seno-7284 was administered to Zmpste24-KO mice from 12-week-old to the end of life. We also administrated seno-7284 to chronological aged mice at 1-year-old for 20 weeks and their physical function was examined with rotarod running test and hand-grip test. Results: Seno-7284 reduced the accumulation of senescent cells in visceral adipose tissue of dietary obese mice as senescence-associated beta-galactosidase (SA-beta-gal) staining exhibits (Figure 1a). This effect results in ameliorating insulin tolerance (Figure 1b) and adipose tissue inflammation after 4-week administration of seno-7284. We also found administrating Seno-7284 for two weeks also reduced the accumulation of senescent cells in the atherosclerotic lesion in the aorta of ApoE-KO mice (Figure 1c) and inhibited advancing atherosclerosis (Figure 1d). Surprisingly, seno-7284 significantly improved the lifespan of Zmpste24 KO mice (Figure 1e). Seno-7284 also improved the physical function of chronologically aged mice by administrating it from 1-year-old for 20 weeks (Figure 1f). In-vitro studies didn't exhibit seno-7284 kills senescent cells directly, but further analysis including RNA-seq or metabolomic analysis speculated that seno-7284 stimulates endogenous senolytic function of NK-cells and CD8+ T-cells. Conclusion: Our results indicate that seno-7284 would become a promising senolytic drug that exhibits novel therapeutic machinery for aging and age-related cardiometabolic diseases. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid for Scientific Research (KAKENHI) C, Niigata University Tsukada medical research grant